Decreased Expression of Glial-Derived Neurotrophic Factor Receptors in Glaucomatous Human Retinas - Akurathi, Abhigna; Boese, Erin A.; Kardon, Randy H.; Ledolter, Johannes; Kuehn, Markus H.; Harper, Matthew M. (Current eye research, 2022)
The purpose of this study was to examine the expression of glial-derived neurotrophic factor (GDNF), the GDNF receptors GFRα1 and GFRα2, ciliary neurotrophic factor (CNTF), and the CNTF receptor CNTFRα in normal and glaucomatous human tissue. Human retinas were collected from 8 donors that had been clinically diagnosed and treated for glaucoma, and also from 9 healthy control donors. Immunohistochemical analysis for each trophic factor and receptor was performed. The percent of each retinal section labeled with each antibody was quantified for the total retinal thickness, and separately for the retinal ganglion cell (RGC) complex + retinal nerve fiber layer (RNFL). The expression of each protein was correlated with measures of the subject's ocular histories. The percentage area immunopositive for GFRα2 was significantly decreased in the total retinal thickness containing all retinal layers and in the combined RGC complex + RNFL in glaucomatous eyes in both the peripapillary region and more peripheral retinal locations. We also observed a decrease in GFRα1 expression in the peripapillary RGC Complex + RNFL in glaucoma patients compared to healthy control patients. We also observed a relationship between GDNF and its receptors with several outcomes obtained from the medical record. No differences in CNTF or CNTFR labeling were observed. Decreases in GDNF receptor expression in glaucomatous tissue may limit the potential for neuroprotective therapy by supplementation with GDNF.